PKM Implementation of Complementary “Cupping” Nursing in Controlling Hypertension During Covid-19 Pandemic - Ahmad Kholid Fauzi; Handono Fatkhur Rahman; Mohammad Alfian Faisol Mustaqim; Fauzan Abdul Latif; Dwiki Qutsi Ali Multazam; Anando Setyo Adiwirawan; Ahmad Labib Umam Musthofa; Badrul Nurul Hisyam (GUYUB: Journal of Community Engagement, 2021)
The number of sufferers infected with Covid-19 is increasing in Indonesia. Kompas states that there were 3,874 people infected with Covid-19 as of September 27, 2020. There are 275,213 people infected with Covid-19 to date. This case increase gives special attention to various government and scientific disciplines. Kompas 18 May 2020 stated that based on reports that around 35 % of Covid-19 patients are people with hypertension, diabetes mellitus, and other cardiovascular diseases. This community service staff will implement complementary nursing "wet cupping" in controlling hypertension during the Covid-19 pandemic. This service used the application of complementary nursing with wet cupping by pre-experimental method, namely one group pretest and posttest design. The people chosen were 16 participants who had hypertension problems. The community service participants will be measured their blood pressure before and after being given wet cupping. The final measurement was carried out after six hours of wet cupping. The instruments needed in this service are a set of cupping tools, a blood pressure meter, and an observation sheet. The evaluation results carried out on participants who had been given wet cupping were a decrease in blood pressure. After a statistical test was carried out, there was a significant effect of complementary "wet cupping" treatment on blood pressure with p-value at systolic = 0.004 and p-value at diastolic =0.036. The p-value for systolic and diastolic blood pressure was smaller than the alpha value of 0.05. Wet cupping is a prophetic treatment method with benefits and does not cause bad side effects. So that this cupping can be a recommendation for people with hypertension to control blood pressure levels by undergoing cupping regularly and can increase good immunity for people with hypertension.